The Phenomenon of Employee Resistance to Change. Case Study of Alstom SA - Karuga, Oskar (Zjawisko oporu pracowników wobec zmian. Studium przypadku Alstom SA, 2025)
The main goal of the research is to shed light on the topic of employee resistance to change, its sources and ways of minimizing it. The research was conducted in one of the production plants of Alstom SA, Alstom Wroclaw RSC, a Polish branch of a company specializing in rolling stock production. The method used to conduct research was a survey. The results of the survey show that the most significant factor influencing employee resistance to change in the researched organization is the large workload and employees’ fear of increased workload resulting from the changes. Employees fear the consequences of reduced productivity after changes are implemented due to an organizational culture that focuses on productivity and results.
Quote as: Karuga, O. (2025). The Phenomenon of Employee Resistance to Change. Case Study of Alstom SA. In A. Witek-Crabb & J. Radomska (Eds.), New Trends in Business Management. Strategy, Branding, Teamwork (pp. 122-136). Publishing House of Wroclaw University of Economics and Business.
Keywords: resistance to change; change management; sources of resistance to change; minimizing resistance to change; opór pracowników wobec zmian; zarządzanie zmianą; źródła oporu pracowników wobec zmian; minimalizowanie oporu pracowników wobec zmian